To reconnect or not reconnect distal Purkinje fibers, that is the question when modeling the Purkinje fiber network - Bayer, Jason D.; Gillette, Karli; Coronel, Ruben; Plank, Gernot; Vigmond, Edward J. (Frontiers in Physiology, 2025)
Background and aimsMultiple rule-based approaches exist to model the structure of the His-Purkinje system (HPS). While some approaches reconnect Purkinje fibers in the Purkinje fiber network, others do not. The aim of this study was to determine the impact of distal Purkinje fiber reconnections on anterograde activation, retrograde activation, and reentrant arrhythmias.MethodsIn a human biventricular model with or without distal Purkinje fiber reconnections, normal sinus rhythm was simulated by His bundle pacing (anterograde activation), followed by an S1S2 protocol applied to the right ventricular apex (retrograde activation). Activation times in the myocardium and HPS were compared for both anterograde and retrograde HPS activation. Arrhythmia vulnerability windows and duration were determined by identifying the S1S2 coupling intervals that induced a reentry of at least two full rotations. Arrhythmia maintenance was further studied by inducing reentry with 4 Hz line pacing applied to the left ventricular epicardial surface. Reentry duration for each protocol was determined over a 20 s window. The S1S2 and line pacing protocols were repeated in the biventricular model without an HPS.ResultsAnterograde activation times and arrhythmia initiation vulnerability windows were mostly unaltered when removing distal Purkinje fiber reconnections. However, retrograde activation times were 18% longer in the HPS and 8% longer in the myocardium when removing distal Purkinje fiber reconnections. Reentrant arrhythmias from the S1S2 protocol and rapid line pacing lasted longer for the model with (11.2 and >20 s) versus without (3.2 and 8.2 s) distal Purkinje fiber reconnections. The S1S2 protocol did not induce reentrant arrhythmias in the human ventricles model without an HPS, and reentry induced with 4 Hz line pacing lasted only 3.6 s.ConclusionRetrograde activation times increased and the duration of reentrant arrhythmias shortened in the absence of Purkinje fiber reconnections in the Purkinje fiber network. This could be an important structural HPS property to incorporate into computational heart models when investigating retrograde activation and/or reentrant arrhythmias. Modifying the structure of the Purkinje fiber network to remove Purkinje fiber reconnections in patients with life threatening ventricular arrhythmia might be antiarrhythmic.